Grassland Ecophysiology and Grazing Ecology - Lemaire, G (CABI, 2014)
This book consists of edited and revised versions of the invited papers presented at an International Symposium on Grassland Ecophysiology and Grazing Ecology held in Curitiba, Parana, Brazil, 24–26 August 1999. This Symposium, organized by the Federal University of Parana (Curitiba) and the Federal University of Rio Grande do Sul (Porto Alegre) in Brazil had as its main objective to assemble the leading scientists in the world in the research area of plant ecophysiology and ecology focused on the management and sustainability of natural grassland ecosystems. Sixteen international speakers coming from different parts of the world were invited to deliver review papers on different scientific topics concerning plant responses to the environment, plant adaptation to defoliation, plant–animal interactions and the sustainability of the grazing management of natural pastures